Insertion of Moderate Islamic Values into the Merdeka Curriculum and Its Implications for Educational Practice - Alpin Qirom; Muhammad Makinuddin (Lembaga Yasin AlSys, 2026)
Indonesia’s sociocultural diversity requires an educational approach that can address intolerance and radicalism while strengthening social cohesion. This study analyzes the integration of moderate Islamic values (wasathiyyah) into the Independent Curriculum (Kurikulum Merdeka) and examines its implications for students’ character development. Employing qualitative library research, the study drew primary data from official policy documents, particularly Regulation of the Minister of Education, Culture, Research, and Technology Number 12 of 2024, and secondary data from relevant academic journal articles and books. The data were systematically examined through content analysis, with source triangulation used to enhance the validity of the findings. The analysis reveals that moderate Islamic values are integrated at three interconnected levels: philosophical, curricular, and pedagogical. At the philosophical level, the curriculum aligns a humanistic educational paradigm with the principle of rahmatan lil ‘alamin. At the curricular level, the values of tawassuth, tasamuh, and i’tidal are aligned with the dimensions of the Pancasila Student Profile and the Pancasila Student Profile Strengthening Project (P5). At the pedagogical level, differentiated instruction, pedagogical flexibility, and dialogical-contextual learning facilitate meaningful engagement with religious and national values. Collectively, these forms of integration have important implications for fostering inclusive character, reducing exclusivism, and preventing radicalism within educational institutions while reinforcing harmony between religious commitment and national belonging (al-muwathanah). The study concludes that integrating moderate Islamic values into the Independent Curriculum represents a paradigmatic shift from textual-doctrinal transmission toward contextual-axiological character formation. These findings contribute a conceptual and policy-based foundation for developing contemporary Islamic Religious Education curricula and advancing inclusive educational practices in Indonesia.